Poluição do ar e doenças respiratórias: Estudo ecológico de série temporal - Nascimento, Luiz Fernando Costa [UNESP]; Vieira, Luciana Cristina Pompeo Ferreira; Mantovani, Katia Cristina Cota [UNESP]; Moreira, Demerval Soares [UNESP] (FapUNIFESP (SciELO), 2016)
CONTEXT AND OBJECTIVE: Exposure to air pollutants is one of the factors responsible for hospitalizations due to respiratory diseases. The objective here was to estimate the effect of exposure to particulate matter (such as PM2.5) on hospitalizations due to certain respiratory diseases among residents in Volta Redonda (RJ). DESIGN AND SETTING: Ecological time series study using data from Volta Redonda (RJ). METHODS: Data on hospital admissions among residents of Volta Redonda (RJ), between January 1, 2012, and December 31, 2012, due to pneumonia, acute bronchitis, bronchiolitis and asthma, were analyzed. Daily data on PM2.5 concentrations were estimated through the CCATT-BRAMS model. The generalized additive Poisson regression model was used, taking the daily number of hospitalizations to be the dependent variable and the PM2.5 concentration to be the independent variable, with adjustment for temperature, relative humidity, seasonality and day of the week, and using lags of zero to seven days. Excess hospitalization and its cost were calculated in accordance with increases in PM2.5 concentration of 5 μg/m3. RESULTS: There were 752 hospitalizations in 2012; the average concentration of PM2.5 was 17.2 μg/m3; the effects of exposure were significant at lag 2 (RR = 1.017), lag 5 (RR = 1.022) and lag 7 (RR = 1,020). A decrease in PM2.5 concentration of 5 μg/m3 could reduce admissions by up to 76 cases, with a decrease in spending of R$ 84,000 a year. CONCLUSION: The findings from this study provide support for implementing public health policies in this municipality, which is an important steelmaking center.
Air pollution and respiratory diseases: Ecological time series
Keywords: Air pollution; Bronchiolitis; Mathematical models; Particulate matter; Pneumonia